1994
DOI: 10.1046/j.1471-4159.1994.62010166.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo, Ex Vivo, and In Vitro One‐ and Two‐Dimensional Nuclear Magnetic Resonance Spectroscopy of an Intracerebral Glioma in Rat Brain: Assignment of Resonances

Abstract: An in vivo study of intracerebral rat glioma using proton-localized NMR spectroscopy showed important modifications of the spectra in the tumor as compared with the contralateral brain. To carry out the assignment of the resonances of the glioma spectra, tumoral and normal rat brain tissues were studied in vivo, ex vivo, and in vitro by one-dimensional and two-dimensional proton spectroscopy. N-Acetylaspartate was found at an extremely low level in the glioma. The change of peak ratio total creatinel 3.2 ppm p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 43 publications
4
33
0
1
Order By: Relevance
“…5). This supports the view that the in vivo 1 H MRS-visible lipid signals in human brain tumours arise from cytoplasmic lipid droplets, as observed in studies of C6 glioma cells and rodent brain tumours (5)(6)(7)(8), and are not just residual lipids from cell membrane breakdown products. A study on endothelial cells exposed to hypoxia showed an increase in lipid body formation to be dependent on O 2 concentration (26).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…5). This supports the view that the in vivo 1 H MRS-visible lipid signals in human brain tumours arise from cytoplasmic lipid droplets, as observed in studies of C6 glioma cells and rodent brain tumours (5)(6)(7)(8), and are not just residual lipids from cell membrane breakdown products. A study on endothelial cells exposed to hypoxia showed an increase in lipid body formation to be dependent on O 2 concentration (26).…”
Section: Discussionsupporting
confidence: 85%
“…1, we give an example of a biopsy specimen from a grade II tumour where there are lipid droplet clusters suggestive of possible islands of hypoxia forming among regions of viable cells, and it is possible that such clusters give rise to the lactate signal often observed in vivo by 1 H MRS (2). This is unlike the development of the implanted C6 rodent tumours, where a core of necrosis develops, with a ring of severely hypoxic cells within the bulk of the tumour (8,10). In contrast, human astrocytomas, by their invasive nature and co-option of existing vasculature, develop in a more heterogeneous manner, with greater intermingling of apoptosis, necrosis, hypoxia, and areas of viable tumour cells.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations